1986
DOI: 10.1016/0266-7681(86)90187-7
|View full text |Cite
|
Sign up to set email alerts
|

Exsanguination of the upper limb in hand surgery comparison of four methods

Abstract: Four methods of exsanguination of the upper limb during hand surgery were compared by a randomised blind trial in one hundred patients. Exsanguination by a method of hand-over-hand compression proved ideal in 92% of cases. The advantages of this technique are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…The scintigraphic method which we used is both more precise and physiological than plethysmography for the measurement of changes in the blood volume in the limbs. 2 In this study we have evaluated various methods of exsanguination of the upper limbs including elevation alone, the use of bandages, the squeeze method, 7 the Urias bag 8,9 and elevation for longer than 30 seconds.…”
Section: (In 1909) and Warren Hardiman Andmentioning
confidence: 99%
“…The scintigraphic method which we used is both more precise and physiological than plethysmography for the measurement of changes in the blood volume in the limbs. 2 In this study we have evaluated various methods of exsanguination of the upper limbs including elevation alone, the use of bandages, the squeeze method, 7 the Urias bag 8,9 and elevation for longer than 30 seconds.…”
Section: (In 1909) and Warren Hardiman Andmentioning
confidence: 99%
“…In this study we have evaluated various methods of exsanguination of the upper limbs including elevation alone, the use of bandages, the squeeze method, 7 the Urias bag 8,9 and elevation for longer than 30 seconds.…”
mentioning
confidence: 99%
“…10 The squeeze method is a hand-over-hand procedure on the elevated arm starting with a squeeze of the examined hand and quickly proceeding proximally, displacing the volume of blood into the upper arm proximal to the tourniquet. 7 The Urias bag is an inflatable arm splint intended for stabilisation of fractures as an emergency procedure. The splint was inflated with compressed air to a pressure of 200 mmHg.…”
mentioning
confidence: 99%
“…9 The authors in the present article found that the brachial artery is more reliably compressed in the cubital fossa. The nature and speed of the technique make it very suitable to facilitating operations where the tourniquet has to be applied more than once.…”
Section: Discussionmentioning
confidence: 46%
“…1). 8,9 During regional or general anesthesia, this is achieved by holding the patient's fingertips if these are uninjured: otherwise the wrist is held. Then, with compression on the artery being maintained, the arm is immediately elevated into the high vertical position (Fig.…”
Section: Techniquementioning
confidence: 99%